Enhanced oxygen reduction performance of nitrogen and sulfur Co-doped graphene oxide by immobilized ionic liquid. (8th June 2021) - Zhang, Wenlin; Zhang, Yongkang; Li, Yandong; Yang, Shuangcheng; Zhang, Lu-Hua; Yu, Fengshou
Highlights: An ionic liquid modified N/S co-doped graphene oxide was designed as ORR catalyst. The modified IL can stabilize *OO − intermediate and enhance catalytic performance. The IL-SNG shows a comparable activity and superior durability to Pt/C catalyst. Abstract: The development of robust metal-free catalysts for electrochemical oxygen reduction reaction (ORR) is a great challenge due to the large energy barriers for the intermediate *OO − formation. In this work, an ionic liquid (IL) modified N/S co-doped graphene oxide (IL-SNG) was synthesized and explored as a metal-free ORR catalyst in alkaline conditions. Compared to the electrode without IL modification (SNG), the onset and half-wave potentials of IL-SNG were positively shifted by 130 and 110 mV, respectively. The IL and co-doping effects enable IL-SNG a comparable activity to that of Pt/C catalyst in alkaline solution. In addition to impressive activity, IL-SNG exhibits a superior tolerance to methanol and excellent long-term stability over Pt/C under the identical conditions, enabling it a potential candidate for ORR in alkaline conditions. DFT calculation shows that IL enhances O2 adsorption and stabilizes the high-energy *OO − intermediate by forming ion pairs and therefore boosts the catalytic activity.